TOXICITY ANALYSIS OF IONIC LIQUIDS TOWARDS VIBRIO FISCHERI USING QSAR - GILL, PAVENJEET KAUR (2021)
The bottleneck establishes an obstacle in their broad application, minimal knowledge on the potential toxicity of ionic liquid (ILs). Due to their appealing and special characteristics, ionic fluids (ILs) have received important attention in academia and industry.